Tailoring mechanical energy harvesting performance of piezoelectric nanogenerator via intrinsic electrical conductivity of ferroelectrics. (June 2021) - Khatua, D.K.; Maria Joseph Raj, N.P.; Khandelwal, G.; Rao, A.N.; Kim, S.-J.
Abstract: Piezoelectric-based mechanical energy harvesting has received tremendous attention as an alternative green energy harvesting technology. However, the magnitude of power generated in this process is extremely low pertaining to the low current response of piezoelectric energy harvesters. Although conducting fillers such as Ag nanowire, carbon nanotube, Cu nanorods, and so on, have used in conventional piezoelectric/polymer composite devices to increase scavenged power density, the achievement is not significant. Finding an alternative and efficient way of tailoring the energy harvesting is therefore highly appreciated. In this article, we introduce the concept of tuning intrinsic electrical conductivity of ferroelectric ceramics while preserving its ferroelectric/piezoelectric strength to enhance the energy harvesting performance of piezoelectrics. We implement this idea by developing an electron-doped (La-doped) Ba(Sn0.09 Ti0.91 O3 ) (BST:La) piezoceramic and further designing 0–3 type composite device with non-ferroelectric polydimethylsiloxane polymer. About three order of increase of intrinsic current density in the doped piezoceramic compared with that of undoped component leads to the scavenged power density enhancement ~10.5 times in the composite with the doped specimen as compared with that comprises of undoped piezoceramic (BST). Our approach opens up a new, convenient way to improve the power density of piezoelectric-based flexible energy harvesters. Graphical abstract: Image 1 Highlights: Conducting ferroelectric (c-FE) based on donor doping is demonstrated in La-doped Ba(Sn0.09 Ti0.91 O3 ) (BST:La) piezoceramics. Novel flexible piezoelectric energy harvesting (FPEH) device is proposed based on c-FE/PDMS composite. About 40 times increase in the instantaneous power density achieved by c-FE–based piezoelectric design. Intrinsic way of enhancing scavenged power density is demonstrated. Improvement of scavenged electrical output is compared to that of conventional conducting filler–based approaches.